Antibacterial and antibiofilm lectins from plants – a review (Research, Society and Development, 2021)
The number of multidrug-resistant bacteria that affect public health has been rising, and there are limited therapy resources to deal with these pathogens. The formation of biofilm by bacteria, makes therapy even harder. In this regard, natural products have been increasingly used as source for new antimicrobial agents and lectins have stood out as a promising option. Thus, this work aims to review on plant lectins with antibacterial and antibiofilm properties against pathogenic microorganisms. Several lectins, extracted from Punica granatum (PgTeL), Portulaca elatior (PeRol), Curcuma longa L. (CLA), Sterculia foetida L. (SfL), Apuleia leiocarpa (ApulSL), Schinus terebinthifolius (SteLL), Archidendron jiringa Nielsen (AjL) e Phthirusa pyrifolia (PpyLL), demonstrated antibacterial activity. Canavalia ensiformis (ConA), Calliandra surinamensis (Casul), Solanum tuberosum (StL-20), Canavalia marítima (ConM) demonstrated antibiofilm activity. Moreover, lectins from Alpinia purpurata (ApuL) e Moringa oleífera (WSMoL) demonstrated both potentials. Therefore, this review gathered substantial evidence that these lectins might constitute therapeutic alternative to treat infections caused by multidrug-resistant and biofilm-producing Gram-positive e Gram-negative bacteria in the future.